Beyond our wildest dreams, an evaluation of conversational learning using Information and Communication Technology (ICT) - Browne, Elizabeth (Proceedings of the International Conference on Networked Learning, 2002)
This article provides summary of research which examines interaction between lecturers and learners involved in an on-line Masters degree in Education. Having used traditional qualitative research methods of the research moves into the relatively new realms of researching online. Applying a methodology known as ’cyber-ethnography’ insight is gained into the experience of staff and students. Those involved identify the advantages of asynchronous communication in providing time for reflection and considered response. Further advantages are identified in the opportunity to consult across the globe on issues to do with practice. The disadvantages link to technology and issues of access, equity and support. The recommendations are for specific focus on tutorial support in virtual learning situations.